The Effect of Steaming and Heat-Compression on the Properties of Jabon Wood for Furniture Materials - Efrida Basri; Abdurachman Abdurachman; Wahyu Dwianto (Masyarakat Peneliti Kayu Indonesia, 2014)
The inferior properties of juvenile jabon wood (Anthocephalus cadamba Miq.) limit its utility. Densification through heat-compression presently conducted is possibly useful to improve its properties. Preceding heat-compression, jabon wood samples were either steamed or non-steamed. Heat-compression temperatures were varied at 170 C, 180 C and 190 C. Compression was carried out until 20% reduction in wood thickness. Physical and mechanical properties and machining properties of the compressed wood samples were determined in accordance with standard procedures of ASTM D143-94 and ASTM D1666-64, respectively. In the present works, both of the ASTM standard referred were slightly modified. X-ray diffractometer (XRD) was used to determine crystallinity degree of wood. The result showed that either steamed or not, densification was successfully increased the properties of juvenile jabon wood and satisfied the requirement of wood for furniture raw materials.Keywords: furniture, heat pressure, steaming, wood properties, young age-jabon